Spectral and antifungal studies of transition metal complexes of N,N?-ethylenebis(salicylideneimine) - Temel, H; Taskin, T; Sekerci, M (Pleiades Publishing Ltd, 2004)
Mixed ligand Schiff base complexes of Ti(IV), Co(11), Ni(II) and Cu(II) derived from salicylaldehyde and 1,2-diaminoethane have been synthesized and their spectral studies carried out. The complexes have been characterized by elemental analysis, molar conductivities, magnetic measurements, H-1 NMR, UV, visible and IR-spectra. The antifungal effects of the mixed ligand Schiff base complexes of Ni(II), Cu(II) and Ti(IV) on Fusarium oxysporum ssp. melonis and Alternaria sp. were investigated. Antifungal effects on pathogen fungi have been observed with each complex in the study. The complexes inhibited fungi growth at a 66.7 mug/ml concentration of Ni(II) complex, and at a 133.3 mum/ml concentration of Cu(II) and Ti(IV) complexes.
Keywords: Schiff-Base Complexes; Circular-Dichroism; Zn(Ii) Complexes; Ni(Ii); Copper(Ii); Cu(Ii); Nickel(Ii); Zinc(Ii); Manganese(Iii); Cobalt(Ii)